To translate the given argument into a formal logic statement, we need to analyze the components of the statement:
The argument is:
"If I work out every day and eat healthily, I will not get sick."
Given:
- [tex]\(\rho\)[/tex] ([tex]\(p\)[/tex]): I work out every day.
- [tex]\(q\)[/tex]: I eat healthily.
- [tex]\(r\)[/tex]: I will get sick.
Let's break down the statement:
1. "If I work out every day and eat healthily" can be represented as [tex]\(p \wedge q\)[/tex].
2. "I will not get sick" indicates the negation of [tex]\(r\)[/tex], which is [tex]\(\sim r\)[/tex].
Putting these together, the statement:
"If I work out every day and eat healthily, I will not get sick" translates to:
[tex]\((p \wedge q) \rightarrow \sim r\)[/tex]
Therefore, the correct answer is:
C. [tex]\((p \wedge q) \rightarrow \sim r\)[/tex]